A Comparative Analysis of Risk and Cost-effectiveness of Outpatient versus Inpatient Hindfoot Fusion. Issue 3 (14th September 2018) - Moon, Andrew; McGee, Andrew; Patel, Harshadkumar; Huntley, Samuel; Pinto, Martim; Naranje, Sameer; Stibolt, Robert; Lehtonen, Eva; Pitts, Charles; Shah, Ashish
Category: Hindfoot Introduction/Purpose: Hindfoot fusion procedures are increasingly being performed in the outpatient setting. However, the cost-effectiveness of hindfoot fusion procedures compared with risk and benefit have not been clearly investigated. The primary objective of this study was to investigate the cost-effectiveness of outpatient versus inpatient hindfoot arthrodesis. Secondary objectives were to compare patient characteristics and short-term complications of patients in each cohort. Methods: This was a retrospective review of all patients who underwent inpatient and outpatient hindfoot fusion procedures at a single institution from 2013-2017. Data collected for each patient included demographic information, operative variables, comorbidities, complications, and any subsequent emergency department visits, readmissions or reoperations. Cost data was collected for each inpatient or outpatient encounter, as well as any subsequent encounters related to the index procedure. Results: Of 151 total hindfoot procedures performed over the study period, 37 were inpatient and 114 were performed in the outpatient setting. There were 3 more readmissions, 22 more ED visits, and 0 more reoperations after outpatient surgery vs inpatient surgery. The average total cost for an outpatient hindfoot fusion procedure was significantly lower than the average total cost for inpatient hindfoot fusion, without a significant increase in complication rate. We are currently in the process of performing the total cost analysis, and will have the completed cost and risk/benefit information within the next two weeks. Conclusion: Outpatient hindfoot fusion surgery may be more cost-effective when compared to inpatient fusion surgery without a significant increase in complications, ED visits, or readmissions.